2021
DOI: 10.3389/fphar.2021.638881
|View full text |Cite
|
Sign up to set email alerts
|

Model Based Evaluation of Hypersensitivity Adverse Drug Reactions to Antimicrobial Agents in Children

Abstract: Drug use in children is–in most cases–supported by extrapolation of data generated from clinical trials in adult populations. This puts children at higher risk of developing adverse drug reactions (ADRs) due to “off-label” use of drugs and dosing issues. Major types of ADRs are drug hypersensitivity reactions, an idiosyncratic type of ADRs that are largely unpredictable and can cause high morbidity and mortality in a hard-to-identify specific population of patients. Lack of a complete understanding of the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…This study was conducted to examine the value of screening suspected ADR cases prior to any investigations using history and clinical presentation alone in an ambulatory care setting and to compare the Naranjo Scale to the Liverpool Causality Assessment. The 2 published assessment tools: the older Naranjo Scale and newly developed tool by the Liverpool group were correlated with well‐studied diagnostic tests such as the allergy skin test, lymphocyte toxicity assay, in vitro platelet toxicity assay, radioallergosorbent test and oral challenge 22–25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was conducted to examine the value of screening suspected ADR cases prior to any investigations using history and clinical presentation alone in an ambulatory care setting and to compare the Naranjo Scale to the Liverpool Causality Assessment. The 2 published assessment tools: the older Naranjo Scale and newly developed tool by the Liverpool group were correlated with well‐studied diagnostic tests such as the allergy skin test, lymphocyte toxicity assay, in vitro platelet toxicity assay, radioallergosorbent test and oral challenge 22–25 …”
Section: Discussionmentioning
confidence: 99%
“…The 2 published assessment tools: the older Naranjo Scale and newly developed tool by the Liverpool group were correlated with wellstudied diagnostic tests such as the allergy skin test, lymphocyte toxicity assay, in vitro platelet toxicity assay, radioallergosorbent test and oral challenge. [22][23][24][25] Both assessment tools have a high sensitivity in predicting ADR cases but poor specificity. Liverpool Causality Assessment Tool (97.2 ± 2.4%) proved to be the more sensitive tool compared with its predecessor, Naranjo Scale (81.2 ± 5.69%).…”
Section: Discussionmentioning
confidence: 99%
“…Adverse drug reactions account for 3–6% of all hospital admissions and occur in 10–15% of hospitalized patients. 1 , 2 Drug hypersensitivity reactions represent approximately one-third of all adverse drug reactions, 3 and epidemiological studies have shown that approximately 7% of the population experience drug hypersensitivity reactions at least once in their lives. 4 Drug hypersensitivity is considered a public health problem owing to the associated morbidity and socioeconomic costs worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…4 Drug hypersensitivity is considered a public health problem owing to the associated morbidity and socioeconomic costs worldwide. [1][2][3][4] Patients with drug hypersensitivity experience a sensation of anxiety, fear, and tension, which can influence their quality of life and disrupt daily performance. Previously, studies have been conducted on the quality of life and psychology in patients with drug hypersensitivity, [5][6][7] but many aspects remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%